EVALUASI PROGRAM PMT-P PADA IBU HAMIL KEKURANGAN ENERGI KRONIK DI PUSKESMAS PEKALONGAN SELATAN (Program Studi Gizi Jurusan Ilmu Kesehatan Masyarakat Fakultas Ilmu Keolahragaan Universitas Negeri Semarang (UNNES) bekerjasama dengan Persatuan Ahli Gizi (PERSAGI), 2022)
Pregnant women chronic energy deficiency in South Pekalongan Health Center is still relatively high, which is 109 cases compared to other health centers in Pekalongan City. Efforts made by the government in improving the nutrition of pregnant women kek with the provision of additional food. Evaluation of the program is carried out to find out whether the implementation of the PMT program of pregnant women is in accordance with the Juknis PMT. The purpose of this study was to evaluate the PMT-P program in KEK pregnant women in South Pekalongan Health Center. This type of research is descriptive using mixed methods, namely qualitative and quantitative research. Determination of informants with purposive techniques. Primary and secondary data retrieval techniques with in-depth interviews and literature studies. The results of the study showed the input aspect, the form of service has not been in accordance with the Juknis PMT. From the aspect of the process, monitoring and reporting have not been in accordance with the Juknis PMT. Aspect of output, the provision of PMT pregnant women is on target, the paired t test obtained the results of no difference in the size of LILA of pregnant women KEK before and after being given PMT.